Wear in Silicon Nitride Sliding Against Titanium Alloy Pairs at Different Loads Under Artificial Seawater Lubrication - Zhang, Jianjun; Wang, Zhaoxun; Chen, Wei; Liao, Huimin; Zeng, Ming; Ma, Sude (Frontiers in Materials, 2019)
Tribological behaviors of Si3N4 ceramic sliding against titanium alloy at different normal loads under seawater lubricated conditions are investigated on a pin-on-disc tester. Generally, for Si3N4/titanium alloy pair, the friction coefficient increases from 0.43 to 0.67 with load increasing (from 10N to 30N). Correspondingly, the wear rate is in the consistent case. When Si3N4 slides against titanium alloy, the wear mechanism is dominated by mechanical wear even though under seawater lubrication. With load increasing, the shear force of solid shear and furrow drag aggravated, which should be responsible for the rising trend of friction coefficient and wear rate.